(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
In Latin America in general and in Paraguay specifically, environmental problems are a great concern not only due to the loss of forests and biodiversity but, above all, due to the lack of awareness within the population about the proportions and consequences of this issue. Taking into account that the human population and its behavior towards the environment is responsible, directly or indirectly, for the majority of the acts and attitudes that cause the current environmental situation, it is of great importance to increase the number of studies in the human dimension of environmental conservation and try to determine which factors contribute to pro environmental attitudes. In this case study, the environmental awareness in a sample of 358 people who are exposed to different degrees to natural environments through their sports activities are analyzed using an instrument proposed by Dunlap and Van Liere (1978) called the New Environmental Paradigm Scale (NEP scale). A 14- item version of the instrument was used in a population that was classified into 3 groups according to the degree of contact with nature to which they are exposed through their sports activities. No significant differences were obtained in the measurements through this instrument among the groups. The structure of environmental awareness resulted in a high score for the “ecocentrism” dimension while lower scores were obtained for “awareness of the limit of resources” and “environmental anthropocentrism”. These results are described as high environmental awareness measured through the NEP scale within the outdoor activity members. It is recommended that further empirical investigations to compare populations that do not participate in any of these activities be performed and also that their scores are correlated in order to determine whether outdoor activities raise awareness of the environmental problems and if they are used as a tool in environmental education in Paraguay.